Analisis Kesalahan Berbahasa pada Unggahan Caption Instagram Akun Pribadi, Bisnis, dan Publik Figur - Rika Febri Finansyah; Sherly Melinda Putri; Retty Afrillia Gautami; Ilyas Ilyas (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2025)
This study aims to analyze linguistic errors in Instagram captions from personal, business, and public figure accounts. Data collection was carried out by taking screenshots of accounts with erroneous captions. The analysis focused on identifying errors in the use of spelling, hyphens, capitalization, and word choice. The research found 10 data points with numerous errors in captions created by personal, business, and public figure accounts. These errors are presented with corrected sentences or appropriate phrasing to ensure captions are not only visually appealing but also clear, easy to understand, and effective in conveying messages.